2D Material‐Based Photodetectors for Infrared Imaging. Issue 1 (18th October 2021) - Cheng, Zhongzhou; Zhao, Tong; Zeng, Haibo
Abstract : As a dynamic research field, infrared (IR) detection and imaging presents broad prospect in spectra‐chemistry, biomedicine, and artificial intelligence. Due to the excellent properties, 2D materials are expected to overcome the serious manufacturing cost and integration problems of Si‐based photodetectors, providing opportunities for the universal application of IR imaging. Up to now, dozens of 2D materials are used to manufacture IR photodetectors. The ultrathin and flexible 2D material‐based optoelectronic devices, which are easy to machine and integrate, will demonstrate the application beyond imagination. In this review, first, the principle of IR detection and imaging is introduced, in which the single pixel and array imaging are discussed. Then the promising materials, toward broadband detection and special detection, are introduced in brief and the devices for imaging are summarized, including the mode based on light intensity and the strategy originated from polarization. Finally, it is prospected that the 2D materials have the capability to show the integral IR world, which contains large amount of valuable information such as molecular vibration spectra and significant applications such as artificial retina. Abstract : 2D materials are expected to overcome the serious manufacturing cost and integration problems of Si‐based photodetectors. The ultrathin and flexible 2D material‐based optoelectronic devices will demonstrate the application of infrared (IR) imaging beyond imagination. This review introduces the principle of IR detection and imaging. The promising materials and devices for IR detection and imaging are listed and discussed.